Stalked barnacles (Cirripedia, Thoracica) from the Upper Jurassic (Tithonian) Kimmeridge Clay of Dorset, UK; palaeoecology and bearing on the evolution of living forms. Issue 3 (June 2019) - Gale, Andy
Abstract: New thoracican cirripede material from the Kimmeridge Clay (Upper Jurassic, Tithonian) is described. This includes a log, encrusted on the lower surface with hundreds of perfectly preserved, articulated specimens of Etcheslepas durotrigensis Gale, 2014, and fewer specimens of Concinnalepas costata (Withers, 1928). Some individuals are preserved in life position, hanging from the underside of the wood, and the material provides new morphological information on both species. It appears that Martillepas ovalis (Withers, 1928), which occurs at the same level (Freshwater Steps Stone Band, pectinatus Zone) attached preferentially to ammonites, whereas E. durotrigensis and C. costata used wood as a substrate for their epiplanktonic lifestyle. Two regurgitates containing abundant barnacle valves, mostly broken, and some bivalve fragments, have been found in the Kimmeridge Clay. These were produced by a fish grazing on epiplanktonic species, and are only the second example of regurgitates containing barnacle valves known from the fossil record. The evolution of modern barnacle groups is discussed in the light of the new Jurassic material as well as recently published molecular phylogenies. New clades defined herein are called the Phosphatothoracica, the Calamida and the Unilatera.